The Exploration of Students’ Perception toward Autonomous English Language Learning - Duti Volya; Hadiyanto Hadiyanto; Eddy Haryanto; Mukhlash Abrar (Media Akademika Publisher, 2025)
The aim of the study is to investigate the students’ perception of autonomous English learning. This research is explanatory in nature whereby a mixed mode of quantitative and qualitative approach are employed in different sectional respectively. Quantitative data is the main method of this study, while qualitative data used to support quantitative data based on Implicit Theory. In this research, quantitative data were obtained from the students' survey by filling questionnaires on the self-assessment checklist. Meanwhile qualitative data obtained from interviews. The data were obtained in the form of interviews and students' surveys. A survey research was conducted by collecting 235 questionnaires from students and afterward, the researcher interviewed 9 students. To analyze the data collected from the questionnaire and the interview, the researcher used descriptive statistics and thematic analysis. The results indicate that students perceive themselves as autonomous in English learning. Students of English study program are relatively better at understanding instructors teaching objectives and requirement and monitoring the use of learning strategies. Additionally, they are relatively weaker in setting up personal learning objectives and study plans, using learning strategies in an effective way and monitoring and evaluating the English learning process.